Big Data Solutions : Innovative Approaches to Overcoming Agricultural Challenges in Developing Nations by Harnessing the Power of Analytics - World Bank (World Bank, Washington, DC, 2017)
The food system is fundamental for human life. It provides energy, nutrition, an income source for billions of people, and is the largest user of the world’s natural resources. In response, improvements in agriculture operations have to be made at both the policy and individual farmer level in order to realize gains in efficiency and productivity. The recent worldwide diffusion of new technologies, combined with big data and analytics, is providing the opportunity for developing countries to leap frog some of the intermediate development phases providing farmer’s in the developing world with greater access to timely, cost effective, and personally relevant information on best practices, markets, prices, inputs, weather, and news of impending disaster. In particular, the penetration of mobile phones, and the innovative applications of geospatial and sensing technologies are providing opportunities to use big data in support of agriculture initiatives, including the ones funded by the World Bank. This solution brief defines what big data is in the context of the developing world, presents a series of case studies on how big data has already been used to date, and identifies some lessons learned and potential opportunities for the use of big data in supporting the achievement of agricultural outcomes in the developing world.